2013
DOI: 10.3758/s13421-013-0368-8
|View full text |Cite
|
Sign up to set email alerts
|

Animates are better remembered than inanimates: further evidence from word and picture stimuli

Abstract: In three experiments, we showed that animate entities are remembered better than inanimate entities. Experiment 1 revealed better recall for words denoting animate than inanimate items. Experiment 2 replicated this finding with the use of pictures. In Experiment 3, we found better recognition for animate than for inanimate words. Importantly, we also found a higher recall rate of “remember” than of “know” responses for animates, whereas the recall rates were similar for the two types of responses for inanimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
155
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(181 citation statements)
references
References 59 publications
23
155
2
1
Order By: Relevance
“…The results of recall performance replicated the findings of previous studies (Bonin et al, 2014;Nairne et al, 2013;VanArsdall et al, 2013;VanArsdall et al, 2014), and expanded them to Chinese words. More critically, animacy was used as a cue for metamemory judgments, with participants assigning higher JOLs to animate than they did to inanimate words.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…The results of recall performance replicated the findings of previous studies (Bonin et al, 2014;Nairne et al, 2013;VanArsdall et al, 2013;VanArsdall et al, 2014), and expanded them to Chinese words. More critically, animacy was used as a cue for metamemory judgments, with participants assigning higher JOLs to animate than they did to inanimate words.…”
Section: Resultssupporting
confidence: 84%
“…Recent research by Nairne, VanArsdall, Pandeirada, Cogdill, and LeBreton (2013) has demonstrated that animacy is also a critical mnemonic dimension, and animate words are remembered better than are inanimate words. This is referred to as the animacy effect (see also Bonin, Gelin, & Bugaiska, 2014;VanArsdall, Nairne, Pandeirada, & Blunt, 2013;VanArsdall, Nairne, Pandeirada, & Cogdill, 2014). This finding is in line with the functionalist view of memory put forward by Nairne and his colleagues Nairne, Pandeirada, Gregory, & VanArsdall, 2009;Nairne, Pandeirada, & Thompson, 2008), which states that the human memory system has been tuned to solve critical adaptive problems.…”
Section: Fluency Beliefssupporting
confidence: 68%
See 1 more Smart Citation
“…Animates are better remembered than inanimates (Bonin, Gelin, & Bugaiska, 2014). The distinction between animates and inanimates is fundamental in human cognition (Rakison & Poulin-Dubois, 2001) and is incorporated in the agreement systems of many languages (Corbett, 2000(Corbett, , 2006.…”
Section: Manipulating Processing Cost Through Animacymentioning
confidence: 99%
“…The dashed game objects in problem states on the bottom of the figure indicate the game object which was moved Note that in the event sentences all referents described by the grammatical subjects were animate, whereas in the state sentences all subjects were inanimate. Many empirical studies investigating animacy suggest that animate objects are remembered better than inanimate objects (see, for example, Bonin et al 2014). Therefore, shorter RTs on the subject position of event sentences than of state sentences were expected, resulting in a main effect of animacy.…”
Section: Resultsmentioning
confidence: 99%